A PEIRCEAN SEMIOTIC ANALYSIS OF VISUAL LANGUAGE REPLACEMENT IN TIKTOK COMMENT SECTIONS - Fadhillah, M. Adhib; Hartono, Arli Ocha Putri; Baldina, Raiza Wahda; Herawati, Cindy Audylia; Zulkhaeriyah (Universitas Negeri Surabaya, 2026)
This study investigates the utilization of visual stickers as communicative instruments in TikTok comment sections, with particular focus on audience responses to a public figure's clarification video. Adopting a descriptive qualitative methodology, the research examines data collected from three TikTok videos published by Indonesian media outlets in November 2024. The analytical framework is established upon Charles Sanders Peirce's triadic semiotic model alongside Danesi's theoretical perspective on visual language replacement in digital communication. Findings indicate that commenters predominantly select stickers conveying mockery and anger, thereby generating collective patterns of distrust and frustration regarding the video content. Sticker selection additionally operates as a social marker facilitating users' identity expression, whether projecting critical, humorous, or skeptical personas within the interaction. These visual components extend beyond mere emotional expression, serving to establish users' discursive positioning within the broader conversation. The study substantiates that TikTok stickers constitute multimodal semiotic resources that fundamentally influence how individuals articulate attitudes, formulate interpretations, and engage in digital platform interactions. This phenomenon represents a significant transition from text-based communication toward visually-mediated expression in contemporary online discourse.